Implementation of Collision Regulations (Colreg) to Avoid the Danger of Collisions in Narrow Shipping Channels on the KM. Pangrango - I Putu Arya Weda Witana; Anak Agung Istri Sri Wahyuni; Faris Nofandi; Tri Haryanto (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
Narrow channels in Indonesian waters pose significant collision risks for passenger ships like KM. Pangrango due to dense local traffic and limited maneuverability. This study aims to analyze COLREG Rules 5-9 implementation and identify implementation constraints during watchkeeping. Qualitative descriptive approach employed purposive sampling of two navigation officers (Second and Third Officer) as key informants. Data collected via direct observation, semi-structured interviews, and document analysis, validated through triangulation. Findings reveal generally compliant COLREG application through visual-radar monitoring, safe speed adjustments, risk assessments, evasive maneuvers, and right-side channel positioning. However, suboptimal consistency in comprehensive surveillance, bridge coordination, and early decisive actions persists due to fluctuating alertness amid unpredictable fishing vessels and buoys. Practically, enhanced bridge resource management training is recommended. Future research should examine multi-vessel comparisons.